A avaliação do mestrado e doutorado profissionais em administração e contabilidade: desafios e oportunidades - Junior, Nélio Herzmann (2020)
Evaluation of professional master's and doctoral programs in Brazil is going through a moment of transition and improvement due to the publication of ordinance no. 60, of March 20, 2019,which regulates and institutes professional master's and doctoral degrees, within the scope of CAPES. It is research aims to verify the perception of professional stricto sensu graduate program coordinators about the evaluation process, as evaluation criteria used to evaluate the performance of the master's programs and doctorate Brazilian professionals. This is a descriptive research with an approach qualitative, and the strategy chosen to absorb the data was the survey through interview with specialists, in relation to the formation of the categorical set, the categories were defined during the content analysis. As main results, it was verified that there search project is a common criterion for evaluating the candidate, the ANPAD test score and professional experience influence the choice of candidates. Completion works course of professional programs, should be materialized in a dissertation with research applied to problem solving, with an impact on the applied environment, duly supported by a theoretical framework, training professionals in their efficiency and effectiveness in organizational practices. The characteristics of production involving the researcher and practical application, the interviewees were highlighted by all. It was also verified, that products should be publicized in harmony with the values of those involved, a logical management and an agreement regarding the publication of results. The Master professional contributes to the professional's development, reflecting on their performance in the organization and, consequently, in his career evolution. Valuation was noted by the development agencies, with regard to technical productions. With the realization of this research it was possible to conclude that there are many similarities between the programs professionals and their evaluation, and academic programs. Although there are similarities, programs are already starting to become different and to value different objectives for their graduates, thus having the possibility that, with the emergence of professional doctors in the academy, in the coming years, these differences will become increasingly clear.